The impact of hospital-based post-discharge pharmacist medication review on patient clinical outcomes: A systematic review - Jaclyn Costello; Michael Barras; Holly Foot; Neil Cottrell (Elsevier, 2023)
Background: Clinical pharmacists have been shown to identify and resolve medication related problems post-discharge, however the impact on patient clinical outcomes is unclear. Aims: To undertake a systematic review to identify, critically appraise and present the evidence on post-discharge hospital clinics that provide clinical pharmacist medication review; report the patient clinical outcomes measured; and describe the activities of the clinical pharmacist. Methods: Published studies evaluating a patient clinical outcome following a post-discharge hospital clinic pharmacy service were included. All studies needed a comparative design (intervention vs control or comparator). Pubmed, Embase, CINAHL, PsycnINFO, Web of Science, IPA and APAIS-Health databases were searched to identify studies. The type of clinic and the clinical pharmacist activities were linked to patient clinical outcomes. Results: Fifty-seven studies were included in the final analysis, 14 randomised controlled trials and 43 non-randomised studies. Three key clinic types were identified: post-discharge pharmacist review alone, inpatient care plus post-discharge review and post-discharge collaborative clinics. The three main outcome metrics identified were hospital readmission and/or representation, adverse events and improved disease state metrics. There was often a mix of these outcomes reported as primary and secondary outcomes. High heterogeneity of interventions and clinical pharmacist activities reported meant it was difficult to link clinical pharmacist activities with the outcomes reported. Conclusions: A post-discharge clinic pharmacist may improve patient clinical outcomes such as hospital readmission and representation rates. Future research needs to provide a clearer description of the clinical pharmacist activities provided in both arms of comparative studies.